Prediction of Rust Thickness in Reinforced Concrete Structures to Enhanced the Asset Management for Coastal Infrastructures - Wahyuniarsih Sutrisno; I Ketut Hartana; Priyo Suprobo (Journal of Infrastructure & Facility Asset Management, 2019)
Corrosion in reinforced concrete structure is a serious problem, especially for coastal infrastructure. Managing the coastal infrastructure from corrosion is a really essential action to make sure that the infrastructure can be used properly throughout its service live. This research focused on analyzing the rust thickness on steel reinforcement due to corrosion. Series of corrosion test using galvanostatic was performed in this research. Furthermore, a predictive model based on Farraday’s Law with uniform corrosion assumption also developed in this research and compared with the experimental data. Based on the simulation result, it was found that the predictive model of rust thickness based on Farraday’s Law is capable to simulate the corrosion process and thickness of the rust.